PENGARUH SERVICE QUALITY DAN KEPUASAN TERHADAP LOYALITAS PELANGGAN PT BANK RAKYAT INDONESIA TBK CABANG DENPASAR - Ni Made Juliyanti; Ni Ketut Murdani; Widiana, I Nyoman Wahyu (PT. Intelek Cendikiawan Nusantara, 2024)
This research aims to examine the impact of Service Quality and Customer Satisfaction on Customer Loyalty at PT Bank Rakyat Indonesia Tbk, Denpasar Branch, utilizing the grand theory of Human Resource Management (HRM). This research employs a quantitative associative approach with a population of 160 employees and a sample of 62 respondents selected using the Slovin formula. The results indicate that: 1) Service Quality has a positive and significant effect on Customer Loyalty; 2) Customer Satisfaction has a positive and significant effect on Customer Loyalty; and 3) Service Quality and Customer Satisfaction collectively have a positive and significant effect on Customer Loyalty. The implications of this research suggest that enhancing Service Quality and Customer Satisfaction at PT Bank Rakyat Indonesia Tbk, Denpasar Branch, can effectively increase Customer Loyalty.